Huge Mucinous Cyst Adenoma, Case Report Series - Ali Elimam, Ali Mohammed; Babbiker, Isam Mohamed; Elhaj Farah, Reem Mohammed; Abbas, Ayat Salih; Abubeker Sayed, Omer Mohamed (Clinical Journal of Obstetrics and Gynecology, 2025)
Mucinous cystadenoma constitutes 15% of epithelial ovarian tumors. In resource limited setting they may reach huge size as there is no regular medical checkup. This case series highlights these aspects along with diagnostic and surgical considerations.